An insight into the management of urinary bladder diverticulum: a retrospective observational study - Sengupta, Soumish; Basu, Supriya; Gupta, Saurabh (International Journal of Advances in Medicine, 2020)
Background: The aim of the study is to retrospectively analyse the best mode of treatment for patients presenting with urinary bladder diverticulum. Methods: This study includes 46 patients who presented to the outpatient department between January of 2018 to March of 2020. They had lower urinary tract symptoms (LUTS) and were later found on investigations with imaging like ultrasound and voiding cystourethrogram (VCUG) as having bladder diverticulum with some cases associated with bladder outlet obstruction. Secondary causes were treated surgically or conservatively with clean intermittent catheterisation (CIC). Diverticulum was addressed with diverticulectomy when conservative management failed with recurrent LUTS or if the diverticulum was of a large size with significant post void residual urine. Results: Most of the patients with diverticulum associated with prostatomegaly or stricture urethra fared well after treatment of the underlying cause except one who underwent subsequent diverticulectomy. Four out of 5 patients with neurogenic bladder did well with CIC alone barring one who underwent diverticulectomy for a large sized diverticulum and refractory LUTS. Two patients with bladder growth involving the neck of diverticulum underwent partial cystectomy along with diverticulectomy. Four out of the remaining 8 patients with primary diverticulum were taken up for diverticulectomy directly and one underwent subsequent diverticulectomy for failed CIC. Conclusions: Not all urinary bladder diverticulum required surgical management per se. Most fared well with treatment of the underlying cause. So only those with large size, recurrent LUTS and failed management with CIC should be considered for diverticulectomy.